COLLOCATION OF ENGLISH, ARABIC, AND INDONESIAN COVID-19 TERMS - Darsita Suparno; Ulil Abshar; Mulyadi Mulyadi; Santje Iroth (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
This paper studies language and translation of the term related to Covid-19. The background of this research is many new vocabularies related to Covid-19 is borrowing term. This study attempts to find answers to the following question: a) What kind of collocations are related to the term Covid-19 pandemic in English, Arabic, and Indonesian? b) How is the pattern of word order forming collocations with the term Covid-19 pandemic in English, Arabic, and Indonesian? This study addressed the emergence of new English, Arabic, Indonesian collocation related to Covid-19 using H. Men’s collocation theory. This study used newspapers, namely Republika, BBC, al-Jazeera online that show Covid-19 as the standard procedure for collecting data. This study used corpus linguistic to analyze collocation, concordance, and syntax analysis, models. The Covid-19 domain has chosen because the Indonesian term in this domain uses a lot of loanwords. The source of the data was a basic-words and compound term. The investigation informed several aspects of findings, such as identifying the pattern of collocation, borrowing, and collocation term of coronavirus concept.